2012
DOI: 10.1186/1471-2369-13-75
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to hepatitis B virus surface antigen and interleukin 12 and interleukin 18 gene polymorphisms in hemodialysis patients

Abstract: BackgroundThe interleukin (IL)18 rs360719 CC genotype is associated with the development of antibodies to hepatitis B virus surface antigen (anti-HBs) in hemodialysis (HD) patients. IL18 shares biological properties with IL12 in promoting the T-hepler 1 (Th1) system. We studied whether polymorphisms in the IL12A 3` untranslated region (UTR) and IL12B 3`UTR may contribute to anti-HBs development (titre ≥ 10 IU/L) in HD patients either individually or jointly with the IL18 polymorphism.MethodsIn 518 HD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…In 1998 Hohler and et al (28) have reported enhanced expression of DRB 1×3, DRB 1×7 and DRB 1×14 in nonresponders to hepatitis B vaccine. More recently, interleukin genotypes (examples IL10, IL-12, IL-18) were associated with the anti-HBs development in response to HBsAg in HD patients (29-31). A very well established negative factor of immunization failure is increasing age (30, 32-34).…”
Section: Resultsmentioning
confidence: 99%
“…In 1998 Hohler and et al (28) have reported enhanced expression of DRB 1×3, DRB 1×7 and DRB 1×14 in nonresponders to hepatitis B vaccine. More recently, interleukin genotypes (examples IL10, IL-12, IL-18) were associated with the anti-HBs development in response to HBsAg in HD patients (29-31). A very well established negative factor of immunization failure is increasing age (30, 32-34).…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination is important both to prevent susceptible patients from acquiring HBV and to reduce the pool of HBV‐infected patients. About 20% dialysis patients do not develop protective titre of antibodies to hepatitis virus surface antigen . Therefore, hepatitis B vaccination is suggested for patients with chronic kidney disease prior dialysis commencement when the immune system is less compromised which provides higher seroprotection rates and antibody titres .…”
Section: Hepatitis B Infection In Dialysis and Renal Transplantmentioning
confidence: 99%
“…Results of these studies indicate that in renal replacement therapy (RRT) subjects, there is a relatively weak association between polymorphisms of genes encoding Th cell cytokines and development of antibodies to surface antigen of hepatitis B virus (anti-HBs) in response to hepatitis B vaccination or hepatitis B virus (HBV) infection. [25][26][27][28][29][30] Active immunization against HBV may be less effective in ESRD patients due to vitamin D deficiency. 31 Vitamin D related genetic background may contribute to lower response to hepatitis B vaccination.…”
Section: Vaccination Against Hepatitis B Virusmentioning
confidence: 99%